Existence of Homoclinic Orbits for a Singular Differential Equation Involving p-Laplacian. (20th July 2020) - Yin, Honghui; Du, Bo; Yang, Qing; Duan, Feng
Abstract : The efficient conditions guaranteeing the existence of homoclinic solutions to second-order singular differential equation with p -Laplacian ϕ p x ′ t ′ + f x ′ t + g x t + h t / 1 − x t = e t are established in the paper. Here, ϕ p s = s p − 2 s, p > 1, f, g, h, e ∈ C ℝ, ℝ with h t + T = h t . The approach is based on the continuation theorem for coincidence degree theory.